CFD simulation and validation of the in-cylinder within a motored two-stroked SI engine - Mohd Fauzani, Mohd Nawi (2008)
The two stroke engine is the current engine of choice in the motocross bike because it of simplicity of design, size to power ratio, lightweight, low number of moving parts, ease of maintenance and excellent power and torque characteristics. However, the major disadvantage to a two stroke engine that negates all the previously mentioned positive qualities is the emission of substantial hydrocarbons, carbon monoxide and fine particulate matter. These pollutants have significant adverse health effects on environmental quality. The objective of the research is to study about the in-cylinder flow of the two stroke spark ignition (Si) engine. This research is carried out from the experimental analysis data that were set as the boundary condition in the numerical analysis. The experiments were based on the motored condition where there is no combustion inside the cylinder. The numerical analysis is carried out using Computational Fluids Dynamic (CFD) Fluent code. From the research, the result from the both experimental analysis and numerical analysis were validated so that the major characteristic of the in cylinder flow can be understand. Beside the validation, other relating characteristic such as cylinder pressure and burned mass fraction can be determined.